ENVIRONMENTAL HEALTH DIFFERENCES IN MODERATOR BY FOREST AREA AND HEALTH SUPPLIERS IN SOLOK DISTRICT - Afid, Muhammad (STIKes Kapuas Raya, 2018)
Environmental Health Risk Assessment with a view primary data on sanitation and hygiene at the Nagari level. The purpose of this research is to see the difference of environmental health is moderated by forest area and health worker. The research method used quantitatively with Export Factor and the number of samples as much as 74 nagari. The results of the test for the forest area of Thitung 0.336> 0.05 Ttable indicate areas adjacent to the forest area, have a better environmental health level or strata region with lower sanitary risk, with the area that is not adjacent to the forest area. And The Result Annova Ftable > FHitung (3.130> 0.592) the average number of healthcare workers on the same regional jurisdiction (there is no difference) means that the number of health workers is large, sufficient and little has no effect on the strata of the area at risk of sanitation, so it can be said, more health workers do not affect the level of better or worse environmental health. The need for increased socialization and activities related directly to local people or communities in order to increase public awareness and awareness of the health and environmental sustainability.